Who Says They Don’t Read? Slovene Elementary School Students’ Reading Motivation in EFL - Pirih, Anja (Revija za elementarno izobraževanje, 2015)
A typical (Slovene) teenager today no longer finds reading materials on the book shelves in the local library, but forms a reading list of electronic sources, very often in English. However, in contrast with an abundance of studies focusing on first language (L1) reading strategies and motivation, not a lot of literature can be found on reading motivation in a foreign language, even though it is perceived as one of the most important factors influencing second language (L2) development. The aim of this research is to determine the influences on reading motivation in English as a foreign language in the group of young teenagers (11-14-year-olds) and a possible transfer of L1 reading attitudes to L2 reading. The theoretical framework relies on Wigfield and Guthrie’s (1997) self-efficacy theory and Day and Bamford’s (1998) expectancy value model. The data obtained from 197 questionnaires give an insight into not only the frequency of reading in English and the type of reading materials, but also the factors influencing teenagers’ reading motivation in EFL.